THE EFFECT OF AL2O3 AND STIRRING TIME ON DENSITY AND POROSITY OF ALUMINUM ADC12 FOAM - Zulaida, Yeni Muriani; Izzudin, Muhammad Nurul; Suryana, Suryana (National Research and Innovation Agency (BRIN), 2023)
The instability of the foam forming during metallic foam manufacture commonly occurs, which will cause undesirable pores. The stability of the foam structure is one of the important factors. A stabilizer can maintain the foam cell during the melting process. In this study, the metal used is ADC12 with a 12 wt.% of Si element content, and the foaming agent is CaCO3. CaCO3 will produce gas to form bubbles in the melt during the solidification process and use a stabilizer to strengthen cell walls so that foam does not easily fall off or collapse. The stabilizer uses Al2O3 with the variation of Al2O3 are 1 to 3 wt.%. The stirring time is as variable as well. A stirring process is conducted to distribute foaming agents so that the foam distribution is more homogeny throughout the aluminum foam. The variation of the stirring time is carried out for 60, 120, and 180 seconds. The results show that as the time of stirring and the addition of stabilizer increases, the porosity will rise, but the density decrease. Compressive strength results show it has no significant relation with increasing the stabilizer and stirring time. The highest compressive strength is obtained in the sample with a stirring time of 120 seconds with an Al2O3 content of 1 wt.%.